2022
DOI: 10.1080/01611194.2022.2113185
|View full text |Cite
|
Sign up to set email alerts
|

Keys with nomenclatures in the early modern Europe

Abstract: We give an overview of the development of European historical cipher keys originating from early Modern times. We describe the nature and the structure of the keys with a special focus on the nomenclatures. We analyze what was encoded and how and take into account chronological and regional differences. The study is based on the analysis of over 1,600 cipher keys, collected from archives and libraries in 10 European countries. We show that historical cipher keys evolved over time and became more secure, shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The reason behind varying the number of homophones for each plaintext letter is to create more authentic ciphers which are similar to original ciphers, as retrieved from European archives and libraries. Previous studies showed that in homophonic substitu-tion ciphers we can find variable number of code elements for different plaintext letters depending on their frequency in the particular language; frequently occurring plaintext letters usually receive two or three code elements, while less frequent letters are assigned one code element (Kahn, 1996) and (Megyesi et al, 2022).…”
Section: Featuresmentioning
confidence: 99%
“…The reason behind varying the number of homophones for each plaintext letter is to create more authentic ciphers which are similar to original ciphers, as retrieved from European archives and libraries. Previous studies showed that in homophonic substitu-tion ciphers we can find variable number of code elements for different plaintext letters depending on their frequency in the particular language; frequently occurring plaintext letters usually receive two or three code elements, while less frequent letters are assigned one code element (Kahn, 1996) and (Megyesi et al, 2022).…”
Section: Featuresmentioning
confidence: 99%